Social Commerce and Gender Narratives: How Female Entrepreneurs Build Brand Trust Through Live Streaming - Wiwin Riski Windarsari; Hery Maulana Arif (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The rapid growth of live-streaming commerce has transformed social commerce into a highly interactive and emotionally driven digital marketplace. While existing studies primarily explain consumer trust through technological affordances, interactivity, and purchase intention, limited attention has been given to the relational and gendered dimensions of trust construction in live-streaming environments. This study aims to explore how female entrepreneurs build brand trust through gender narratives during live-streaming commerce activities. Adopting a qualitative interpretive approach, this research collected data through semi-structured interviews, live-streaming observations, and digital content documentation involving 12 female entrepreneurs actively conducting live-streaming sales on TikTok Live, Shopee Live, and Instagram Live. The data were analyzed using thematic analysis inspired by the Gioia methodology. The findings reveal that brand trust is constructed through five major dimensions: authenticity through everyday storytelling, relational intimacy, emotional labor, gendered credibility, and trust through real-time interaction. Female entrepreneurs strategically utilized emotional engagement, caring communication, authenticity performance, and relational storytelling to cultivate audience trust and emotional closeness. The study further demonstrates that trust in live-streaming commerce is socially negotiated and performatively enacted rather than merely generated through transactional mechanisms. Theoretically, this study extends the social commerce literature by integrating perspectives from emotional labor, parasocial interaction, authenticity performance, and gender studies into the analysis of digital trust formation. Practically, the findings highlight the importance of relational communication and emotionally meaningful engagement in strengthening brand trust within contemporary social commerce ecosystems.